Comparison of two autologous hematopoietic stem cell mobilization strategies in patients with multiple myeloma: CE plus G-CSF versus G-CSF only: a single-center retrospective analysis - Dill, Veronika; Blüm, Philipp; Lindemann, Anja; Biederstädt, Alexander; Högner, Marion; Götze, Katharina S.; Bassermann, Florian; Hildebrandt, Martin (Transfusion, 2024)
Background Despite recent advances in the treatment of multiple myeloma, high-dose chemotherapy followed by autologous hematopoietic stem cell transplantation (ASCT) remains an essential therapeutic keystone. As for the stem cell mobilization procedure, different regimens have been established, usually consisting of a cycle of chemotherapy followed by application of granulocyte-colony stimulating factor (G-CSF), although febrile neutropenia is a common complication. Following national guidelines, our institution decided to primarily use G-CSF only mobilization during the COVID-19 pandemic to minimize the patients' risk of infection and to reduce the burden on the health system. Study Design and Methods In this retrospective single-center analysis, the efficacy and safety of G-CSF only mobilization was evaluated and compared to a historic control cohort undergoing chemotherapy-based mobilization by cyclophosphamide and etoposide (CE) plus G-CSF. Results Although G-CSF only was associated with a higher need for plerixafor administration (p < .0001) and a higher number of apheresis sessions per patient (p = .0002), we were able to collect the target dose of hematopoietic stem cells in the majority of our patients. CE mobilization achieved higher hematopoietic stem cell yields (p = .0015) and shorter apheresis sessions (p < .0001) yet was accompanied by an increased risk of febrile neutropenia (p < .0001). There was no difference in engraftment after ASCT. Discussion G-CSF only mobilization is a useful option in selected patients with comorbidities and an increased risk of serious infections, especially in the wintertime or in future pandemics.
Online veröffentlicht: 10. April 2024
Gesehen am 16.12.2024